Same-day discharge after transvenous lead extraction: feasibility and outcomes. Issue 2 (28th December 2022) - Atteya, Gourg; Alston, Michael; Sweat, Austin; Saleh, Moussa; Beldner, Stuart; Mitra, Raman; Willner, Jonathan; John, Roy M; Epstein, Laurence M
Abstract: Aims: Same-day discharge (SDD) is safe for patients undergoing electrophysiology procedures. There is no existing data regarding SDD for patients undergoing transvenous lead extraction (TLE). We report our experience with SDD for patients undergoing TLE. Methods and results: The study group included patients undergoing TLE between February 2020 and July 2021 without an infectious indication. A modified SDD protocol for device implants/ablations was applied to TLE patients. Patient characteristics, extraction details, outcomes, and complications were reviewed. Of 239 patients undergoing TLE, 210 were excluded (94 infections and 116 did not meet SDD criteria). Of the remaining 29 patients, seven stayed due to patient preference and 22 were discharged home the same day. The SDD group had an average age of 65.9 ± 12 (47–84), 41% female, and LVEF of 52.2 ± 18% (10–80). The indication for TLE was malfunction (20), upgrade (4), advisory lead (2), and magnetic resonance imaging compatibility (1). Extractions included four implantable cardioverter-defibrillators (ICDs), 17 pacemakers (PPM), and one cardiac resynchronization therapy (CRT)-P system. The leads were 9.6 years (1.5–21.7) old, and 1.8 leads were removed per patient (1–3); the lead extraction difficulty (LED) score was 11.6 ± 7. Twenty underwent cardiovascular implantable electronic device (CIED) re-implantation (2 ICD, 3 CRT-D, 13 PPM, and 2 CRT-P). For CIED re-implants, patients sent a remote transmission the next day, and all patients received a next-day call. There were no procedure or device-related issues, morbidities, or mortalities in the 30 days after discharge. Conclusion: Same-day discharge after TLE for non-infectious aetiologies is safe and feasible in a select group of patients with early procedure completion who meet strict SDD criteria.